Per-packet rate adaptation for wireless video. Issue 7 (October 2016) - Bhide, Anupama; Wright, Dustin; Ozturk, Yusuf
Abstract Streaming video over error-prone wireless channels is a challenge as the dynamic network conditions and slow adaptation to channel degradations may affect the quality of the streamed video. Unequal error protection (UEP) can potentially address this issue by considering the importance of each video packet and its impact on the quality of reconstructed video. This paper proposes a cross-layer UEP solution for wireless video streaming over IEEE 802.11 networks. Video packets are prioritized based on the relative importance of the video packet. UEP is achieved by adapting the link layer parameters on a per-packet basis, using inherent forward error correction and adaptive modulation capabilities of the 802.11n network. Experimental results revealed that the proposed solution achieves comparable performance to the state-of-the-art methods at a lower complexity.